Roh Jahat Yang Dari Pada Tuhan? Tafsir Historis-Kultural 1 Samuel 16:14-23 Dengan Kaitannya Terhadap Kesehatan Mental - Olimbovo, Senopati Salomo (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Many Christians have, since childhood, acquired a dogmatic understanding that God cannot do anything that is not good nor evil. However, what should we do when confronted with 1 Samuel 16:14-23, which explicitly states that "an evil spirit from God" came upon Saul? This article aims to engage in a historical-cultural reading of this text and its contemporary implications for mental health issues. This research employs a qualitative approach with data collection through literature and presents it in a descriptive-analytical form. The author concludes that, when examining the text and context within 1 Samuel 16:14-23, the reading of an "evil spirit from God" is more likely to refer to the psychological condition experienced by Saul, the central character in the text.